ANALISIS SENTIMEN REVIEW PENGGUNA APLIKASI DEPOK SINGLE WINDOW DI GOOGLE PLAY MENGGUNAKAN ALGORITMA SUPPORT VECTOR MACHINE - Arie Wijaya; Prihandoko Prihandoko (Jurnal Ilmiah Informatika Komputer, 2023)
Technology is developing rapidly, including in the world of government. The district government makes a web or mobile-based application with the aim of helping people in getting the services that the community deserves. The Depok Regency Government created a mobile-based public service application called Depok Single Window. Due to the importance of user reviews for the continuity of the DSW application, it is required to analyze the sentiment of reviews of the Depok Single Window application on Google Play Store. Sentiment analysis is carried out using the Support Vector Machine. The data used in this study were 733 reviews obtained from the scrapping. The scrapping is carried out by utilizing python library, namely google play scrapper as access to retrieve data. The results attained from this research are an accuracy value of 89.23% for the sentiment analysis of the Depok Single Window application, which means that the Support Vector Machine is good to be used to classify the Depok Single Window application review data into positive, negative and neutral.